Use of gender distribution in routine surveillance data to detect potential transmission of gastrointestinal infections among men who have sex with men in England. Issue 11 (20th June 2018) - Mook, P.; Gardiner, D.; Kanagarajah, S.; Kerac, M.; Hughes, G.; Field, N.; McCarthy, N.; Rawlings, C.; Simms, I.; Lane, C.; Crook, P. D.
Abstract: Detecting gastrointestinal (GI) infection transmission among men who have sex with men (MSM) in England is complicated by a lack of routine sexual behavioural data. We investigated whether gender distributions might generate signals for increased transmission of GI pathogens among MSM. We examined the percentage male of laboratory-confirmed patient-episodes for patients with no known travel history for 10 GI infections of public health interest in England between 2003 and 2013, stratified by age and region. An adult male excess was observed for Shigella spp. (annual maximum 71% male); most pronounced for those aged 25–49 years and living in London, Brighton and Manchester. An adult male excess was observed every year for Entamoeba histolytica (range 59.8–76.1% male), Giardia (53.1–57.6%) and Campylobacter (52.1–53.5%) and for a minority of years for hepatitis A (max. 69.8%) and typhoidal salmonella (max. 65.7%). This approach generated a signal for excess male episodes for six GI pathogens, including a characterised outbreak of Shigella among MSM. Stratified analyses by geography and age group were consistent with MSM transmission for Shigella . Optimisation and routine application of this technique by public health authorities elsewhere might help identify potential GI infection outbreaks due to sexual transmission among MSM, for further investigation.